Wierzyca jej brzegi oraz bliższe i dalsze okolice / [red. Lech J. Zdrojewski ; teksty Sonia Klein-Wrońska et al. ; foto Lech J. Zdrojewski et al. ]. - Klein-Wrońska, Sonia (Uroki Kociewia, 2014)
Wydawnictwo albumowe.